2019
DOI: 10.1002/admi.201901105
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Nanocomposite Coatings for Confinement and Pumpless Transport of Low‐Surface‐Tension Liquids

Abstract: pollution. Repellent surfaces hinder liquid spreading and for that purpose, are frequently used for fluid management on open surfaces. In some cases, both repellent and adhesive domains are required for efficient fluid management. [1] Wettability engineering, i.e., the spatial modification of surface energy and morphology, is a suitable option for fluid management and has been explored extensively to deliver innovative advances in materials chemistry, fabrication techniques, and a fundamental understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…To demonstrate, that the variety and complexity of shapes obtainable with this core–shell approach is comparable to LSTLs confined by omniphobic–omniphilic surfaces, we created several patterns with varying interior angles (60°, 90°, 120°) and a maze‐like structure (Figure 1C). [ 21,22,24,26 ] Compartments with an organic layer feature size down to 1 mm were fabricated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate, that the variety and complexity of shapes obtainable with this core–shell approach is comparable to LSTLs confined by omniphobic–omniphilic surfaces, we created several patterns with varying interior angles (60°, 90°, 120°) and a maze‐like structure (Figure 1C). [ 21,22,24,26 ] Compartments with an organic layer feature size down to 1 mm were fabricated.…”
Section: Resultsmentioning
confidence: 99%
“…[ 18–20 ] Furthermore, these methods often solely constrain the area wetted by the LSTL and there are only a few demonstrations of patterned LSTLs. [ 21–26 ] Jokinen et al. demonstrated the use of superhydrophobic–hydrophilic patterns to create designer multiphase droplets to confine an organic liquid droplet inside an aqueous droplet or for miniaturized liquid–liquid–liquid extraction application.…”
Section: Introductionmentioning
confidence: 99%
“…Another area for continued research and investigation is the application of wettability gradients to low-surface-tension liquids, where omnidirectional spreading behavior is more commonly seen. Clearly, a different approach is needed here to attain rapid, directional transport …”
Section: Passive Liquid-transport Mechanismsmentioning
confidence: 99%
“…Regime I resembled the early stage spreading of unconfined viscous droplets through hemiwicking, yielding Washburn spreading characteristics (i.e., X ∼ T 0.5 ); the second regime displayed a linear trend (i.e., X ∼ T), ensuing from a balance between the driving capillary force and the viscous resistive force; the third spreading regime followed a density-augmented Tanner spreading trend (i.e., X ∼ T 0.1 ), which arises when the spreading film thickness becomes thin enough so that the dissipation at the contact line dictates the spreading behavior. Such mode of capillary-driven transport on wedge-shaped wettability confined tracks was not restricted only to water droplets; the principle was also harnessed to transport low surface-tension liquids with γ lg as low as 23.8 mN/ m. 163 For a surface immersed in water, a similar design with opposite contrast of wettability (i.e., a superhydrophobic wedgetrack laid on a superhydrophilic background) was shown to induce capillary-driven transport of air bubbles dispensed underneath the wettability patterned surface. 164 Unlike the spreading of liquid droplets on a wedge track, propagation of the air-bubble front, however, showed a linear temporal variation; a scaling argument revealed that the spreading velocity for the bubble on the superhydrophobic wedge track arises from an inertia−capillary force balance and varies as the inverse of the square root of the track width.…”
Section: Transport Due To Surface Wettability Gradientmentioning
confidence: 99%
See 1 more Smart Citation